Physico-Chemical and Bacteriological Characterization of an Ouéga-Fandji’s Drilling Water in Benin - GBOHAIDA, Virginie; Beakou, Buscotin Horace; KOUDORO, YAYA ALAIN; AGBANGNAN, DOSSA COKOU PASCAL; AVLESSI, FÉLICIEN (My University, 2020)
Water, potential source of life, must undergo various physico-chemical and bacteriological analyzes that will define its quality for human consumption in order to avoid the risk of water-borne diseases to consumers. Physico-chemical and bacteriological quality of an Ouega-Fandji’s drilling water, use as drinking water, were investigated. Two (02) samples are constituted for the two analyzes’ types. Twenty physico-chemical parameters (pH, Temperature, Electrical conductivity, Colour, Turbidity, Nitrites, Nitrates, Ammonium, Calcium, Magnesium, Total iron, Bicarbonates, Alcalinity, Chlorides, Sulphates, Fluorides, Iodides, Total hardness, Total Dissolved Solids) and three bacteriological parameters (Fecal coliforms, Total coliforms, Fecal streptococci) are evalued on samples. Some physical parameters (temperature, pH, turbidity and conductivity) able to change during transport have been determined "in situ" using a portable multimeter (HANNA, HI 991300). The results obtained showed that unwanted substances (nitrites, nitrates, ammonium, fluorides, sulfates and iron) were almost absent. The physico-chemical parameters measured in this water sample comply with the quality standards for drinking water in Benin Republic. The conclusion is the same for bacteriological parameters, although the number of total coliforms (13 CFU) present in 100 mL of this water sample exceeds that recommended in Benin Republic. Therefore, disinfection of this water by the usual disinfection methods like chlorination with calcium hypochlorite is mandatory.
Keywords: Drilling; Drinking Water; Physico-chemical; Bacteriological